ANALYTICAL STUDY OF GALLSTONES IN PATIENTS FROM TRANSYLVANIA, ROMANIA - BREZEȘTEAN, Ioana; HAR, Nicolae; TANȚĂU, Alina; GOREA, Maria; VENTER, Monica M.; CÎNTĂ PÎNZARU, Simona (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Here we report the vibrational spectroscopy characterization on human gallstones from patients in Transylvania, Romania. A number of 93 gallstones resulted after surgical intervention were preliminary classified in 6 groups after provenance, shape and color aspect and investigated using optical microscopy and FT-(micro)-Raman spectroscopy in conjunction with the FT-IR. Optical microscopy of the gallstones cross sections revealed concentric layers growing depositions alternating with axial crystalline agglomerated biomaterial. Two distinct type of crystallinity on one hand and different spatial crystals distribution, on the other hand were optically observed. The studied specimens randomly showed very narrow amorphous zones. The microstructure, chemical composition, the nucleation and growing mechanism of gallstones were correlated with the vibrational spectroscopy data. Vibrational assignment allowed identifying cholesterol in all the samples. Other weak bands attributable to bilirubinate salts were randomly observed with different extent in all the groups. Brown, yellowish-brown and yellow gallstones showed higher content of bilirubinate as revealed by the relative intensity ratio of the bilirubinate band at 1620 cm-1 versus cholesterol band at 1464 cm-1 with values between 0.57 and 0.875. FT-vibrational techniques accurately provided the proof of the cholesterol specificity in the choletitiasis prevalence in the area and allowed getting additional insight into their growing mechanism.